Study of Failure Risk Factors for Residential Infrastructure Buildings - Dedy Suryadi; Manlian R.A. Simanjuntak; Basuki Anondho (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The risks and uncertainties of construction projects have the potential to cause damage to construction projects. Risk analysis and management are the main features of construction project management to effectively deal with uncertainties and unexpected events to achieve project success. Design/methodology/approach: Some pertinent risk variables for each classification are six internal, four project risk factors, and four external. Researchers detected 14 external risk factor reasons, 36 internal risk factor causes, 16 project factor causes, and 36 external risk factor causes. Findings: Researchers suggest project risk management through this study by implementing overall risk management. A properly executed project plan and identified risks as early as possible at a later stage turn into success. Managing risks does not mean avoiding them but identifying them correctly to determine all associated opportunities and hazards for project success. Research limitations/implications: A good risk management approach anticipates the risk of building failure. It can happen in residential infrastructure projects. The first step in risk management is to study the risk factors for the loss of residential infrastructure buildings. Following an analysis, the project manager generates recommendations or plans for risk reduction in response to the primary risks in infrastructure projects. Originality/value: This paper is original Paper type: Research paper